Variasiepatrone in Maleier-Afrikaans - Kotze, Ernst Frederick (My University, 2013)
The Malay community of Cape Town, nubering -127 000, constitutes a relatively homogeneous language group within the wider Afrikaans-speaking population of the Peninsula, primarily on account of the fact that every member embraces the Islamic faith, and only changes religious affiliation at the danger of social Ostracism. Conversely, any proselyte to Is;am is cordially welcomed and absorbed into the community. Since the Chomskyan conception of a Homogeneous speech community has been shown to be a myth by linguists such as W Labov and R H Berdan, the problem of linguistic variation within the Malay community is investigated in the present study. The data consist basically of 22 hours of recorded speech, gathered by means of structured interviews with a stratified sample of 59 respondents. For the purpose of Diachronic comparison, written records dating from 1856 onwards were also taken into account. Using the statistical method of comparing population mean scores, 15 linguistic variables were quantified in different styles of speech for each subpopulation. Four general and four specific hypothesses were tested against the data. Further variational phenomena in the data corpus which emerged from the investigation are described and exampkified, together with exerpts from 19th century sources. In this way it could be indicated that a large percentage (at least 56%) of nostandard features which were current in the last century are still common today. In the contemporary data,evolutionary processes could be identifiedin respect of certain linguistic variables by applying Labov`smethodology in describing the mechanism and social context of linguistic change. A prerequisite for the application of Labov`s methodology is the confirmation of the hypothesis (abductively arrived at) that the speech of the community concerned is socially stratified in accordance with particular sociologically determined groupings. This hypothesis is confirmed by the linguistic data, and the added insighr was gained that the degree of relogoous orthodoxy correlates positively with adherence to the vernacular norm. Other findings of the study include a validation of (a) the hypothesis that language pragmatic factors have a significant and peculiar influence on the relative frequency of linguistic correlates of situational and stylistic variation; and (b) the hypothesis that the address system of a language community is a linguistic reflection of the social norms which determine the hierarchical structure of the community.